2009
DOI: 10.1002/bjs.6684
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal acid hypersensitivity is not a contraindication to Nissen fundoplication

Abstract: Patients with oesophageal acid hypersensitivity benefit from Nissen fundoplication as much as those with pathological acid exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…Recently, postsurgical symptom remission has been reported in 16 of 17 PPI-resistant patients selected on the basis of impedancepH monitoring findings, but no objective postoperative assessment of reflux parameters was attempted [17]; symptom remission could well be attributed to a placebo effect. In another study, 28 patients with esophageal acid hypersensitivity unresponsive to PPI therapy were assessed before and after fundoplication with pH-only monitoring performed off PPI therapy [18]. Thus far, no prospective study compared acid and nonacid reflux parameters found after laparoscopic fundoplication with those detected on PPI therapy in PPI-unresponsive patients; therefore, the postsurgical modifications in acid and nonacid reflux parameters associated with postoperative symptom persistence/remission are not known.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, postsurgical symptom remission has been reported in 16 of 17 PPI-resistant patients selected on the basis of impedancepH monitoring findings, but no objective postoperative assessment of reflux parameters was attempted [17]; symptom remission could well be attributed to a placebo effect. In another study, 28 patients with esophageal acid hypersensitivity unresponsive to PPI therapy were assessed before and after fundoplication with pH-only monitoring performed off PPI therapy [18]. Thus far, no prospective study compared acid and nonacid reflux parameters found after laparoscopic fundoplication with those detected on PPI therapy in PPI-unresponsive patients; therefore, the postsurgical modifications in acid and nonacid reflux parameters associated with postoperative symptom persistence/remission are not known.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, HE patients are considered to have GERD and they have similar benefits from antireflux surgery as patients with pathologic degrees of acid exposure. 34 In this context, the baseline impedance value and the PSPW index could be helpful in clinical practice to classify patients correctly who would respond to medical and/or surgical treatments similar to patients with HE. However, the results from this study warrant further validation by prospective outcome studies 581 582 583 584 585 586 587 588 589 590 591 592 593 594 595 596 597 598 599 600 601 602 603 604 605 606 607 608 609 610 611 612 613 614 615 616 617 618 619 620 621 622 623 624 625 626 627 628 629 630 631 632 633 634 635 636 637 638 639 640 641 642 643 644 645 646 647 648 649 650 651 652 653 654 655 656 657 658 659 660 661 662 663 664 665 666 667 668 669 670 671 672 673 674 675 676 677 678 679 680 681 682 683 684 685 686 687 688 689 690 691 692 693 694 695 696 Supplementary Materials...…”
Section: Discussionmentioning
confidence: 99%
“…By using the current Rome criteria these patients were no longer classified as having a functional esophageal disorder but they were considered to be part of the GERD spectrum, which is supported by the fact that these patients generally benefit from antireflux surgery. 30 In a randomized, double-blind study, 6 months of treatment with 20 mg citalopram once a day was significantly more efficient in treating reflux symptoms than placebo because 38.5% of patients using citalopram reported remaining symptoms vs 66.7% of patients using placebo. 26 The most frequently remaining symptom was heartburn, followed by regurgitation and chest pain.…”
Section: Heartburn In Gastroesophageal Reflux Disease Patientsmentioning
confidence: 98%